The effect of auditor reputation, audit fee , audit committee, and financial distress on audit quality with company size as a moderating variable - Nurzahra, Sinta; Budiantoro, Harry (Jurnal Akuntansi dan Manajemen, 2026)
This study is motivated by the growing demand for financial reporting transparency amidst recurring manipulation cases in Indonesian public companies. Audit quality plays a crucial role in enhancing investor trust in financial statements presented by firms. The purpose of this research is to examine the effects of auditor reputation, audit fee, audit committee, financial distress, and firm size on audit quality in companies listed in the Jakarta Islamic Index (JII) during 2019–2023, with firm size also tested as a moderating variable. A quantitative approach was employed, using secondary data from JII companies’ financial reports, and the analysis was conducted using regression methods. The findings reveal that audit fees, audit committees, financial distress, and firm size significantly influence audit quality, while auditor reputation shows no effect. Furthermore, firm size moderates the relationship between several independent variables and audit quality. These results highlight the importance of internal corporate factors and auditor independence in producing high-quality audits and provide implications for regulators, auditors, and investors to improve governance and transparency.